Two Inexpensive and Non-destructive Techniques to Correct for Smaller-Than-Gasket Leaf Area in Gas Exchange Measurements - Savvides, Andreas M.; Fotopoulos, Vasileios (Frontiers in Plant Science, 2018)
The development of technology, like the widely-used off-the-shelf portable photosynthesis systems, for the quantification of leaf gas exchange rates and chlorophyll fluorescence offered photosynthesis research a massive boost. Gas exchange parameters in such photosynthesis systems are calculated as gas exchange rates per unit leaf area. In small chambers (<10cm2), the leaf area used by the system for these calculations is actually the internal gasket area (AG), provided that the leaf covers the entire AG. In this study, we present two inexpensive and non-destructive techniques that can be used to easily quantify the enclosed leaf area (¬AL) of plant species with leaves of surface area much smaller than the AG, such as that of cereal crops. The AL of the cereal crop species studied has been measured using a standard image-based approach (iAL) and estimated using a leaf width-based approach (wAL). iAL and wAL did not show any significant differences between them in maize, barley, hard and soft wheat. Similar results were obtained when the wAL was tested in comparison with iAL in different positions along the leaf in all species studied. The quantification of AL and the subsequent correction of leaf gas exchange parameters for AL provided a precise quantification of net photosynthesis and stomatal conductance especially with decreasing AL. This study provides two practical, inexpensive and non-destructive solutions to researchers dealing with photosynthesis measurements on small-leaf plant species. The image-based technique can be widely used for quantifying AL in many plant species despite their leaf shape. The leaf width-based technique can be securely used for quantifying AL in cereal crop species such as maize, wheat and barley along the leaf. Both techniques can be used for a wide range of gasket shapes and sizes with minor technique-specific adjustments.